Low premorbid IQ may exacerbate the cognitive effects of apolipoprotein ε4 (APOE ε4): a multi-ethnic cross-sectional study from HABS-HD - Lubnaa Badriyyah Abdullah; Zhengyang Zhou; Ney Alex Alliey; Robert Barber; James Hall; Sid O’Bryant (Frontiers in Neurology, 2025)
IntroductionApolipoprotein allele 4 (APOE ε4) is associated with lower IQ scores during childhood and adolescence, but the influence of APOE ε4 and low IQ on late-life cognition is unknown. This study examines the association between APOE ε4 and cognitive outcomes based on premorbid intellectual ability (pIQ) and ethnic background.MethodsParticipants were drawn from the Health & Aging Brain Study–Health Disparities (HABS-HD), categorized by low (z ≤ −2.00) or average (z = 0.00 ± 1.00) pIQ based on word reading scores. Statistical analyses were conducted to evaluate whether APOE ε4 was associated with the cognitive domains of episodic memory, executive functioning, processing speed, and language by pIQ and ethnicity.ResultsAPOE ε4 was associated with worse cognitive performance across domains. In the overall sample analysis, the deleterious effect of ε4 on processing speed and executive functioning was stronger among those with low pIQ. In stratified analysis, the negative impact of APOE ε4 was stronger among non-Hispanic White individuals with low pIQ for episodic memory and Hispanic individuals with low pIQ for processing speed.DiscussionThe influence of APOE genotype on cognitive outcomes is moderated by ethnicity and premorbid IQ, positioning low pIQ, a proxy for intellectual disability (ID), as a population more vulnerable to the negative effects of APOE ε4 in older adulthood.ConclusionThe effect of Alzheimer’s disease (AD) risk genes on cognitive performance may not mirror what is observed in AD-Down syndrome, highlighting the urgent need to expand AD research to reach more representative populations with I/DD.